2019
DOI: 10.1002/adfm.201905056
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy of Single‐Crystalline GaN Film on CMOS‐Compatible Si(100) Substrate Buffered by Graphene

Abstract: Fabricating single-crystalline gallium nitride (GaN)-based devices on a Si(100) substrate, which is compatible with the mainstream complementary metal-oxide-semiconductor circuits, is a prerequisite for next-generation high-performance electronics and optoelectronics. However, the direct epitaxy of single-crystalline GaN on a Si(100) substrate remains challenging due to the asymmetric surface domains of Si(100), which can lead to polycrystalline GaN with a two-domain structure. Here, by utilizing singlecrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…In general, the N 1s of N-doped graphene is characterized by three peak positions, these are, pyridinic-N (398-399 eV), pyrrolic-N (400-401 eV), and graphitic-N (401-402 eV). 7,16,[37][38][39][40][41][42][43][44][45]47 Recently, Chen et al demonstrated a AlN/graphene/sapphire structure using N-doped graphene. 48 They observed N-doped graphene with AlN and showed sp 2 C-N, and Al-N bonds in the N 1s scan using XPS, although N-doped graphene was covered by AlN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the N 1s of N-doped graphene is characterized by three peak positions, these are, pyridinic-N (398-399 eV), pyrrolic-N (400-401 eV), and graphitic-N (401-402 eV). 7,16,[37][38][39][40][41][42][43][44][45]47 Recently, Chen et al demonstrated a AlN/graphene/sapphire structure using N-doped graphene. 48 They observed N-doped graphene with AlN and showed sp 2 C-N, and Al-N bonds in the N 1s scan using XPS, although N-doped graphene was covered by AlN.…”
Section: Resultsmentioning
confidence: 99%
“…The epitaxy caused by a 2-D material, termed van der Waals epitaxy (vdWE), reduces the dislocation density of the grown material, which strongly affects the device properties, and also allows exfoliation of the grown material from the substrate owing to the weak chemical bond. [1][2][3][4] The advantages of vdWE have been conrmed using various structures, such as gallium nitride (GaN) or aluminium nitride (AlN) growth on graphene/silicon carbide (SiC), 5 graphene/ silicon dioxide (SiO 2 ), [6][7][8][9] graphene/silicon (Si), [10][11][12] graphene/ sapphire (Al 2 O 3 ), [13][14][15][16][17][18] and hexagonal boron nitride (h-BN)/ Al 2 O 3 . 19,20 However, the remaining dislocation density on vdWE is still a hurdle to achieving high-quality semiconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no dangling bond for N atom in sp 2 ‐like CN bond, while there is one dangling bond left for each N atom in sp 3 ‐like CN bonds, as reported previously. [ 9,17,38 ] Therefore, when the Ga and N adatoms are supplied, Ga adatom will connect with this dangling bond to form CNGa bond and thus initiate the growth. XPS study of 5‐nm‐thick GaN deposited on the graphene/Al 2 O 3 at 780 °C also confirms this.…”
Section: Resultsmentioning
confidence: 99%
“…The related research work of 2D GaN and van der Waals solids also lights the way for III-nitride-based novel devices fabrication. However, some obstacles, including large-scale single-crystalline epilayer preparation (2-in wafer-scale GaN van der Waals epilayer is available now [ 65 ]), uniformity of epilayer doping, and contact resistance reduction of the device still need to overcome.…”
Section: Summary and Prospectmentioning
confidence: 99%